A Study on Effectiveness of mLearning through Task Based Approach - Shenbagavalli, M; Selvakumar, Y Stanly (International Journal of Advanced Research in Peace, Harmony and Education; Vol 8 No 1 (2023): International Journal of Advanced Research in Peace, Harmony & Education, 2023)
There is an increased use of mobile learning in all the sectors of society. People want learning to be part of their work-flow and prefer formats that engage them better. mLearning is the answer to meet the demands of today’s learner. Hence there is a need to experiment with learning strategies in mLearning environment. The present study investigates the effectiveness of Task Based Approach, a pedagogical approach designed for the purpose of this study, in terms of achievement of participants of the mLearning course. The mLearning course comprised of several tasks to be done using provided mLearning material and quizzes based on the content. It was deployed using WhatsApp. The sample of this study included 60 teachers teaching in state board and CBSE schools. The Tasks and the mLearning material were developed systematically by following instructional design principles. They were found to be effective in attaining significantly high achievement. Motivation of the participants was also found to be high after going through the mLearning course. The participants appreciated the mLearning material and the learning strategy of Task Based Approach. Participants also demonstrated higher order thinking skills while performing the tasks. The learners found the mLearning material and the tasks to be engaging as well as relevant to their professional life. They were also confident of using the learned skills in their professional life.